PEMANFAATAN PERANGKAT LUNAK OPEN SOURCE “SLIMS” UNTUK REPOSITORY PERGURUAN TINGGI - Ilham Arnomo (UIN Syarif Hidayatullah Jakarta, 2016)
Software SLiMS (Senayan Library Management System), which was originally built to meet the needs of the library collection management in Indonesia, it is technically the system features in it, SLiMS fit for use as a repository college. This is reinforced by the presence of one Indonesian university that uses repository college Slims as indexed in the Open Directory Doar and also enter the Webometrics ranking system of web repositories Indonesia. The use of SLiMS as a repository universities are expected to contribute to the advancement of science and technology world.